Attachment Style, Friendship Quality and the Mediating Effect of Communication Skills in Young Adults Friendship - Ai Shin LIM (Universitas Pendidikan Ganesha, 2021)
Liberman and colleagues (1999) argue for the importance of investigating attachment relationships among peers, as they play a crucial role for individuals from adolescence into adulthood. Markiewicz, Doyle, and Brendgen (2001) demonstrated the important link between attachment style and friendship quality, noting that secure attachment predicted perceptions of friendship quality. This study looked specifically at the associations between attachment, communication and the quality of relationship shared between friends using four different questionnaires; Attachment Style Questionnaire (ASQ) by Feeney, Noller & Hanrahan, (1994), Bartholomew and Horowitz’s (1991) Relationship Questionnaire, Communication Functions Questionnaire (CFQ) by Burleson & Samter (1990), and the Network of Relationship Inventory- revised by Furman & Buhremester, (1992).